Global Value Chains and Deep Integration - Baccini, Leonardo; Fiorini, Matteo; Hoekman, Bernard; Altomonte, Carlo; Colantone, Italo (World Bank, Washington, DC, 2021)
How does trade affect the design of preferential trade agreements (PTAs)? What is the role of global value chains (GVCs)? The authors answer these questions by empirically investigating the causal impact of gross and value-added trade on the depth of PTAs. To solve the critical issue of endogeneity of trade flows for trade policy, the identification strategy exploits a recent transportation shock: the sharp increase in the maximum size of container ships, which has more than tripled between 1995 and 2007. The key variation in our instrument hinges on the fact that only deep-water ports can accommodate new larger ships. The strategy is flexible enough to generate excludable instruments for different value-added components of exports. This allows us to assess how the design (depth) of PTAs is affected not only by gross exports but more specifically by GVC-trade as captured by indicators of trade in domestic and foreign value added. The authors find that trade occurring through GVCs increases the probability of forming deep PTAs, i.e., agreements that include provisions that go beyond the coverage of the WTO. These GVC-trade effects are larger than those of gross exports, which include flows that are unrelated to GVCs. The results indicate that GVCs are one important driver of deep preferential liberalization.